Prevalence of contact allergy in the general population in different European regions. (1st February 2016) - Diepgen, T.L.; Ofenloch, R.F.; Bruze, M.; Bertuccio, P.; Cazzaniga, S.; Coenraads, P.‐J.; Elsner, P.; Goncalo, M.; Svensson, Å.; Naldi, L.
Summary: Background: Population‐based studies about contact allergy are scarce. Objectives: To obtain reliable estimates of the prevalence of contact allergy in the general population in Europe. Methods: A cross‐sectional study of a random sample from the general population, aged 18–74 years, in five different European countries (Sweden, the Netherlands, Germany, Italy and Portugal). In total, 12 377 subjects were interviewed and a random sample ( n = 3119) patch tested to TRUE Test panels 1–3 and Fragrance Mix (FM) II, hydroxyisohexyl 3‐cyclohexene carboxaldehyde (HICC) and sesquiterpene lactone mix. A positive patch test reaction is considered as contact allergy. Results: In total, 27·0% [95% confidence interval (CI) 25·5–28·5] had at least one positive reaction to an allergen of the European baseline series, with a significantly higher prevalence in women than in men. The highest age‐standardized prevalences (≥ 1%) were found for nickel (14·5%, 95% CI 13·2–15·8), thiomersal (5·0%, 95% CI 4·2–5·8), cobalt (2·2%, 95% CI 1·7–2·7), FM II (1·9%, 95% CI 1·5–2·5), FM I (1·8%, 95% CI 1·4–2·3), HICC (1·4%, 95% CI 1·0–1·9), p ‐ tert ‐butylphenol formaldehyde resin (1·3%, 95% CI 0·9–1·7) and para ‐phenylenediamine (1·0%, 95% CI 0·6–1·3). Only nickel and thiomersal showed a statistically significantly different prevalence for contact allergy among the different European populations. Subjects reporting contact dermatitis in their lifetime (age‐standardized prevalence 15·1%, 95% CI 13·8–16·3) had an increased risk for contact allergy (odds ratio 1·9, 95% CI 1·5–2·5). The risk of having a contact allergy was not increased in those with atopic dermatitis (prevalence 7·6%, 95% CI 6·7–8·6; odds ratio 1·0, 95% CI 0·7–1·4). Conclusions: Contact allergy to at least one allergen of the European baseline series was diagnosed in more than one‐quarter of the general European population. Therefore measures to improve the primary prevention of contact allergy have to be enforced.